Diagnostic value of bone marrow core biopsy patterns in lymphoplasmacytic lymphoma/Waldenström macroglobulinaemia and description of its mutational profiles by targeted NGS. Issue 9 (24th January 2020) - Garcia-Reyero, Julia; Martinez Magunacelaya, Nerea; Gonzalez de Villambrosia, Sonia; Gomez Mediavilla, Angela; Urquieta Lam, Marcela; Insunza, Andres; Tonda, Raul; Beltran, Sergi; Gut, Marta; Gonzalez, Ainara; Montes-Moreno, Santiago
Abstract : Aims: The aim of this study was to describe the characteristics of the bone marrow infiltration found in a series of clinically defined lymphoplasmacytic lymphoma (LPL)/Waldenström macroglobulinaemia (WM) and IgM-monoclonal gammopathy of undetermined significance (MGUS) and to perform a targeted next-generation sequencing (NGS) for the identification of additional somatic mutations to MYD88 p.L265P in LPL/WM. Methods: We have reviewed a series of 35 bone marrow biopsies from 28 patients with a clinical diagnosis of LPL/WM (24 cases) or MGUS (4 cases). Bone marrow infiltration characteristics by morphology, immunohistochemistry, flow cytometry (FCM), allele-specific real-time PCR for the detection of MYD88 p.L265P mutation, targeted exonic amplicon-based NGS of 35 lymphoma-related genes and direct sequencing were analysed. Results: Our findings show that bone marrow trephine biopsy evaluation is superior to FCM in the identification of significant lymphoid infiltrates. A combined paratrabecular and interstitial infiltration pattern is the most common feature in LPL/WM while a patchy interstitial pattern characterises IgM-MGUS cases. MYD88 p.L265P mutation was found by allele-specific-PCR in 92% of the LPL cases (22 out of 24) and 25% of IgM-MGUS cases (1 out of 4 cases). In addition to MYD88 p.L265P somatic mutations in CXCR4, KMT2D, PRDM1 /Blimp1, MYC and ID3 were found by NGS and direct sequencing in 4 cases. Conclusions: In conclusion, bone marrow core biopsy evaluation is critical in the identification of unequivocal bone marrow infiltration by LPL/WM. In addition to MYD88 p.L265P, somatic mutations in CXCR4, KMT2D, PRDM1 /Blimp1, MYC and ID3 can appear in a fraction of LPL/WM.